NAS AIRCRAFT CABIN AIR QUALITY HEARINGS (Tufts Archival Research Center, 2007)
Marginalia; Memorandum from Sam Chilcote to the members of the Tobacco Institute’s executive committee describing the hearing on the National Academy of Sciences' (NAS) study of aircraft cabin air quality. Cites the Air Transport Association’s assertion that separation of smokers from non-smokers is the most effective way to serve all parties. Reports that Tobacco Institute scientists testified on the broader issue of clean indoor air to ensure that testimony did not focus solely on the smoking issue. Mentions flight attendant testimony offered in support of smoking restrictions.